EFEKTIVITAS PEMINDAHAN NARAPIDANA TERORISME DALAM PROGRAM PEMBINAAN (Studi di Lembaga Pemasyarakatan Kelas IIA Pasir Putih Nusakambangan ) - Alam, Syamsir (MIH Unsoed, 2020)
The Crime of Terrorism can be categorized as mala per se or mala in se, classifiedas a crime against conscience, being something evil not because it is regulated orprohibited by the Act, but rather because it is essentially classified as natural wrong or acts wrong in themselves, and not a prohibita mala which is classified as a crime because it is regulated accordingly by law. The purpose of the research is to analyze the effectiveness of the implementation of the transfer of terrorism inmates in thedevelopment program at the Grade IIA Correctional Institution of Nusakambangan White Sand. The approach used is empirical approach or socio legal research. Analytical descriptive research specifications. The process of transferring inmates can basically be translated into two meanings, namely the process of execution of punishment where it is not carried out in a place where the verdict is read but in another legal area or in this case another area.